Supply Chain Management for Enhancing the Effectiveness of Free Nutritious Meal Programs - Alwi Wira Kusuma (AIBPM Publisher, 2025)
The Free Nutritious Meal Program (Program Makan Bergizi Gratis/MBG) represents a key Indonesian government strategy designed to raise the nutritional health of school children or foster the cultivation of superior human resources. However, the effectiveness of this program largely depends on efficient kitchen operations and well-managed supply chains. This research intends to examine the specific impact of Supply Chain Management (SCM) on the effectiveness of the MBG Program at Dapur Sebelas Bandung, focusing on delivery timeliness, raw material availability, and raw material quality. A quantitative method utilizing a causal research framework was successfully implemented. Data were collected from 50 respondents involved in procurement, processing, and distribution activities using purposive sampling. Structured questionnaires were evaluated using SPSS through validity or reliability tests, descriptive analysis, or multiple linear regression. The results demonstrate that delivery timeliness and raw material availability significantly and positively influence the effectiveness of the MBG Program, emphasizing the critical importance for efficient distribution processes and accurate supply planning to ensure the overall success of this vital national nutritional initiative. Conversely, raw material quality does not show a significant partial effect. Simultaneously, all SCM variables significantly influence program effectiveness. These findings suggest that strengthening logistics coordination, demand planning, and supply chain control is essential to enhance the operational performance and sustainability of the MBG Program.